P-016 Quantitative Assessment of Stent Induced Neointimal Hyperplasia with Contrast Enhanced Cone-Beam CT: In Vivo Validation with Histomorphometry. (14th July 2013) - Flood, T; Bom, I van der; Strittmatter, L; Hendricks, G; Puri, A; Wakhloo, A; Gounis, M
Abstract : Introduction: Intracranial stenting is an effective therapy for specific cerebrovascular disorders including treatment-resistant atherosclerosis, cerebral aneurysms, and arterial dissections. However, in-stent tissue growth (neointimal hyperplasia (NIH) and/or in-stent restenosis (ISR)), is a significant long-term complication that necessitates routine surveillance. Catheter-based digital subtraction angiography, (DSA), is the current imaging standard for NIH/ISR detection; however, DSA is invasive and relies on 2D vascular representations that may over- or underestimate asymmetric tissue growth and consequentially, confuse clinical management decisions. A less invasive 3D capable, cross-sectional imaging technique with resolution to detect NIH/ISR, could circumvent these limitations, better inform clinicians, and improve patient care. Herein, contrast-enhanced C-arm Cone-Beam Computed Tomography, (CE-CBCT), recently optimised for high resolution 3D stent imaging by reducing the field-of-view during acquisition and performing full-scale reconstruction 1, was quantitatively compared to vessel histology in a porcine model of in-stent NIH to validate the CE-CBCT approach. Materials and Methods: All experiments were approved by our IACUC. The following was performed to model in-stent NIH: - 3 days, adult pig started on daily aspirin; day 0, pig anaesthetised, arterial access obtained, 4 arterial areas identified, damaged via a cutting balloon, and stented (Neuroform), pig recovered alive and returned to the animal facility; day 42, daily aspirin stopped; day 49, pig anaesthetised, CE-CBCT data acquired, animal sacrificed and perfused, stented vessels explanted, embedded in resin, sectioned and stained for analysis. Image J was used to quantify stent and luminal area from CE-CBCT and histological cross-sections that were spatially matched to best approximation; the measurements were compared with statistical software (Prism). Results: Stent struts, lumen, and in-stent growth were clearly visualised and easily demarcated for quantitative analysis in both CE-CBCT and histological cross-sections (fig. 1a). CE-CBCT stent, lumen, and in-stent tissue growth calculated areas closely correlated with corresponding histological measurements (r 2 = 0.96, 0.84, 0.87, respectively; fig. 1b). However, CE-CBCT was found to consistently overestimate lumen area relative to histology, which resulted in a lower Pearson's r 2 value and a non-zero intercept in the latter two measurements. Conclusion: CE-CBCT quantification of in-stent tissue growth correlates well with histology in a porcine model and may be an important new clinical tool for post-stent vascular surveillance. Further evaluation of intravenous CE-CBCT as a non-invasive alternative to DSA in post-stent cerebrovascular patients is ongoing. Disclosures: T. Flood: None. I. van der Bom: None. L. Strittmatter: None. G. Hendricks: None. A. Puri: None. A. Wakhloo: 1; C; Philips Healthcare. M. Gounis: 1; C; Philips Healthcare. References: 1. Patel et al. AJNR 2011;32 (1):137–144. 2. Psychogios et al. Investigative Radiology ;2013:48 (2);98–103. 3. Psychogios et al. AJNR 2010;31 (10):1886–91.